Learner Differences in Second Language Acquisition - Mohammed, Ibtisam Jassim (Journal of Tikrit University for Humanities, 2020)
This study aims at exploring the debatable issue of learner‟s differences in second language acquisition (SLA, henceforth). Differences in learning are critical factors which faculty members should take into account in the process of learning and teaching second or foreign languages , also these differences influence learning processes and lead to different linguistic abilities and skills in the second language . Learners differ from each other due to biological, conditioned factors or unconscious forces, each learner is different from the other, and they have different personalities and styles. Some second language learners make rapid and apparent progress while others progress very slowly and with difficulties, in this respect there are several important areas where the learners may show differences from each other. These include: age, sex, aptitude, motivation, cognitive style, personality, and learning strategies.